Keep calm and carry on? Fissure, perception, and narrative contestation following the demise of the Crown - Gellwitzki, CNL; Houde, A-M; Rogers, L; Rosher, B (Oxford University Press, 2024)
On September 8, 2022, after more than 70 years on the throne, Queen Elizabeth II passed away. The responses among the public, media, and state institutions to the news were varied, with competing views on the role of the monarchy and the legacy of the queen. The questions this article seeks to answer are (1) how the monarch’s death introduced a fissure into the United Kingdom’s autobiographical narrative and (2) how exactly this moment led on the one hand to efforts to reaffirm the dominant UK autobiographical narrative and on the other to efforts to contest this narrative. In framing this analysis using Gestalt psychology, we theorize the role of perception in subjects’ experience of a fissure as well as their subsequent attempts to manage the ensuing anxieties. We show how perception enables and guides avenues for narrative contestation as well as conservative attempts to (re)establish the predominant autobiographical narrative by exploring how the government and the royal family sought to create a sense of continuity and transfer royal authority onto the next generation while activists attempted to subvert this established narrative to problematize the country’s (post)colonial history and societal inequalities.